2009
DOI: 10.1051/0004-6361/200911679
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/deuterium exchange in interstellar ice analogs

Abstract: Context. For several reasons, methanol is believed to be formed on grain surfaces and, in warm environments, released in the gas phase. In the past, multiply deuterated isotopologues of methanol have been detected in gas phase around several low-mass protostars. In all these sources, there is significantly more CH 2 DOH than CH 3 OD. Various hypotheses have been suggested to explain this anomaly, but none is fully convincing. Aims. In this work, we test a new hypothesis experimentally: the spontaneous exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 26 publications
8
71
0
Order By: Relevance
“…Thus, in the experiment of Nagaoka et al (2005), the deuterium enrichment was found to proceed via H/D substitution in solid CH 3 OH leading to the formation of methyldeuterated methanol isotopologues, but no CH 3 OD. An alternative solid-state depletion mechanism was proposed by Ratajczak et al (2009): in their experiment, rapid H/D exchanges between CD 3 OD and H 2 O ices were found to occur at T ∼ 120 K on the hydroxyl (-OD) functional group of methanol, resulting in CD 3 OH and HDO molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in the experiment of Nagaoka et al (2005), the deuterium enrichment was found to proceed via H/D substitution in solid CH 3 OH leading to the formation of methyldeuterated methanol isotopologues, but no CH 3 OD. An alternative solid-state depletion mechanism was proposed by Ratajczak et al (2009): in their experiment, rapid H/D exchanges between CD 3 OD and H 2 O ices were found to occur at T ∼ 120 K on the hydroxyl (-OD) functional group of methanol, resulting in CD 3 OH and HDO molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To make the situation even more puzzling, the same [CH 2 DOH]/[CH 3 OD] ratio is close to 1 in the high-mass protostar Orion IRc2 (Jacq et al 1993). This difference between high-and low-mass protostars A&A 528, L13 (2011) might reflect different deuteration degrees and/or ice compositions, as suggested by Ratajczak et al (2009 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this ratio has been observed to lie in the range 5 to 30 towards low-mass and intermediate protostars (Parise et al 2006;Ratajczak et al 2011) and close to or below one in high-mass protostars (Ratajczak et al 2011). Recent laboratory studies (Nagaoka et al 2005;Ratajczak et al 2009) have shown that a much lower abundance of CH 3 OD than for CH 2 DOH, as observed in low-and intermediate-mass protostars (Ratajczak et al 2011), can be qualitatively explained via H/D exchanges occurring on the grain surface following methanol formation. The results of Ratajczak et al (2009), in particular, suggest that such exchanges occur on the hydroxyl (-OD) or amine (-ND) functional groups, via hydrogen bonds with water ice.…”
Section: Introductionmentioning
confidence: 94%
“…Recent laboratory studies (Nagaoka et al 2005;Ratajczak et al 2009) have shown that a much lower abundance of CH 3 OD than for CH 2 DOH, as observed in low-and intermediate-mass protostars (Ratajczak et al 2011), can be qualitatively explained via H/D exchanges occurring on the grain surface following methanol formation. The results of Ratajczak et al (2009), in particular, suggest that such exchanges occur on the hydroxyl (-OD) or amine (-ND) functional groups, via hydrogen bonds with water ice. As a result, in the case of formamide, DCONH 2 species should be significantly more abundant than HCONDH and HCONHD ones, if solid H/D exchanges do happen, because these should take place on the amino group -ND 2 .…”
Section: Introductionmentioning
confidence: 97%